EFFECTS OF SOIL STERILIZATION ON THE FORMATION AND FUNCTION OF TWO STRAINS OF PISOLITHUS TINCTORIUS ON EUCALYPTUS UROPHYLLA*) - NELLY S. AGGANGAN, BERNIE DELL (BIOTROPIA, 1995)
To examine the effects of soil microbial population on mycorrhizal development and function, Eucalyptus urophylla seedlings were inoculated with two Pisolithus tinctorius isolates and grown in sterile, partly sterile and non-sterile soil. The two isolates of Pisolithus were an effective isolate (H445) collected from under eucalypts in Australia and an isolate (H615) collected from under eucalypts in the Philippines. Soils used were infertile acid soils collected from field sites in Pangasinan, Luzon and Surigao, Mindanao. In both soils, the Australian Pisolithus H445 improved the growth of E. urophylla seedlings more than Philippine isolate H615. The uninoculated seedlings exhibited stunted growth typical of P deficiency. Height at 8 weeks was significantly taller in sterile than in non-sterile soil. A significant interaction effect of inoculation and soil sterilization on height at harvest was observed only in Surigao soil. Soil sterilization had a varied effect on mycorrhizal formation. In Pangasinan soil, root colonization by H445 was significantly greater in non-sterile soil than in sterile soil. Whereas in Surigao soil, root colonization was significantly reduced by 54% from partly sterile to non-sterile soil. On the other hand, H615 showed significant mycorrhizal colonization in non-sterile soil compared from those in partly sterile and sterile soils. The degree of infection did not necessarily correspond to growth promotion in E. urophylla seedlings. These results indicate that the performance of the H445 was markedly affected by the microbial flora of the two soils. Thus, its potential use in the Philippines needs to be thoroughly tested in the field before its widespread use in any inoculation program. Key words: Pisolithus tinctorius/Laccaria fraterna/Pinus patula/Inoculum/Seedlings/Growth.